Type IV fimbrial subunit protein ApfA contributes to protection against porcine pleuropneumonia - Sadilkova, Lenka; Nepereny, Jiri; Vrzal, Vladimir; Sebo, Peter; Osicka, Radim (Veterinary research, 2012)
Porcine pleuropneumonia caused by Actinobacillus pleuropneumoniae accounts for serious economic losses in the pig farming industry worldwide. We examined here the immunogenicity and protective efficacy of the recombinant type IV fimbrial subunit protein ApfA as a single antigen vaccine against pleuropneumonia, or as a component of a multi-antigen preparation comprising five other recombinant antigens derived from key virulence factors of A. pleuropneumoniae (ApxIA, ApxIIA, ApxIIIA, ApxIVA and TbpB). Immunization of pigs with recombinant ApfA alone induced high levels of specific serum antibodies and provided partial protection against challenge with the heterologous A. pleuropneumoniae serotype 9 strain. This protection was higher than that engendered by vaccination with rApxIVA or rTbpB alone and similar to that observed after immunization with the tri-antigen combination of rApxIA, rApxIIA and rApxIIIA. In addition, rApfA improved the vaccination potential of the penta-antigen mixture of rApxIA, rApxIIA, rApxIIIA, rApxIVA and rTbpB proteins, where the hexa-antigen vaccine containing rApfA conferred a high level of protection on pigs against the disease. Moreover, when rApfA was used for vaccination alone or in combination with other antigens, such immunization reduced the number of pigs colonized with the challenge strain. These results indicate that ApfA could be a valuable component of an efficient subunit vaccine for the prevention of porcine pleuropneumonia.
Keywords: bakteriální adheziny; Animals; Virulence Factors; Female; Escherichia coli; polymerázová řetězová reakce; exotoxiny; Polymerase Chain Reaction; ženské pohlaví; bakteriální vakcíny; vakcinace; Molecular Sequence Data; rekombinantní proteiny; Recombinant Proteins; Bacterial Vaccines; prasata; Swine Diseases; Actinobacillus pleuropneumoniae; pleuropneumonie; Exotoxins; Actinobacillus Infections; Vaccination; molekulární sekvence - údaje; Male; nemoci prasat; Swine; infekce bakteriemi rodu Actinobacillus; Pleuropneumonia; Sequence Analysis, DNA; bakteriální fimbrie; Fimbriae, Bacterial; zvířata; mužské pohlaví; sekvenční analýza DNA; Adhesins, Bacterial; faktory virulence